DESIGN FREE SURFACE TANK ON FAST MISSILE BOAT 60M - Sutrisno Sutrisno; Andi Mawanto; Wawan Kusdiana; Cahya Kusuma (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
Rolling motion is important role in the stability of the ship. Predicting the motion of a ship design must be done to see the design performance. The magnitude of the resulting motion response will affect the comfort and safety of personnel and materials in the ship. For this reason, simulation and analysis rolling and pitching prediction are carried out when the ship is operating, with and without the addition of a free surface tank (FST) as a stabilizer system with variations in the FST base height, water volume, boat velocity, heading direction and the waves. The prediction of ship motion in this research is ushing shipmo software and to assess operational feasibility, the general criteria standard issued by NATO STAGNAG 4154 (US. Navy) and US Coast Guard. From the simulation results it was found that increasing the height of the FST base from the base line decreases rolling motion. At a height of 4 m the maximum response magnitude below the allowable standard is 3,365 deg, while at a height of 3 m above the allowable standard that is 4,734 deg. The addition of FST and variations in placement of the FST base height from the base line did not significantly affect the pitching motion of the ship. Heading direction, waves and operational speed of the ship need to be considered to get the minimum rolling motion response when the ship is operating. Keywords: Fast Missile Boat 60M, Free Surface Tank, Pitching, Rolling, Shipmo.